Mechanism of PAVA-induced toxicity and inflammation in a cocultured skin cell model - Song, Yunyang; Cheng, Wenjie; Wang, Zhen; Zhou, Tianqi; Wu, Fanghui; Yin, Yifeng; Xu, Dan; Liu, Yanli (Frontiers in Pharmacology, 2025)
BackgroundPelargonic acid vanillyl amide (PAVA), a stable synthetic analog of capsaicin, exhibits potential for therapeutic applications; however, it may present cytotoxic and pro-inflammatory risks. This study aims to investigate the injury effects of PAVA on a cocultured skin cell model in vitro.MethodsHuman keratinocytes and dermal fibroblasts were co-cultured and exposed to PAVA at concentrations ranging from 12.5 to 200 µM for durations of 5, 24, and 48 h. Cell proliferation was quantified using MTS assays. Morphological changes were observed through microscopy, reactive oxygen species (ROS) production was evaluated via fluorescence analysis, apoptosis was assessed using flow cytometry and Western blotting techniques, while inflammatory cytokines (IL-6, IL-8) were quantified by ELISA.ResultsThe proliferation of cells was significantly inhibited by PAVA in a dose- and time-dependent manner, with concentrations of 100 µM and above inducing substantiazl cytotoxicity. Morphological analysis revealed an increase in cell dispersion, irregular morphology, and apoptosis, particularly after prolonged exposure. Treatment with PAVA led to elevated levels of ROS, indicating the presence of oxidative stress. Apoptosis was initiated through both extrinsic pathways (NF-κB, Caspase-8) at an early stage and intrinsic pathways (Caspase-3/9, Bax) at a later period. Furthermore, PAVA markedly increased the secretion of IL-6 and IL-8, suggesting a robust pro-inflammatory response.Conclusion100 μM PAVA elicits pronounced cytotoxic, oxidative, and pro-inflammatory effects on cocultured skin cell model, particularly at higher concentrations and prolonged exposure durations. These findings underscore the necessity of exercising caution when employing PAVA for therapeutic purposes and highlight the imperative for further research to mitigate its adverse consequences as a riot control agent.